Best E-Wallet Selection Decision Support System using MOORA Method and ROC Weighting - Mesran, Mesran; Ramli, M Saidina; Bintang, Muhammad Rizki Olihta; Rohayani, Hetty; Sallaby, Achmad Fikri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
E-wallet is an electronic payment service that is widely used by Indonesian people. Currently, there are many e-wallets on the market, making people confused about choosing an e-wallet that suits their needs. This research implements this system in a simulation environment to test and validate the effectiveness of the approach in selecting the best E-Wallet. Experimental results show that the proposed approach can provide more accurate and relevant recommendations for users in choosing an E-Wallet that suits their preferences. This research aims to build a decision support system for selecting the best e-wallet using the Multi-Objective Optimization by Ratio Analysis method (MOORA) and ROC weighting. MOORA is a multi-objective system that optimizes two or more conflicting properties simultaneously. This method is used to perform complex mathematical calculations. Decision support systems can help in the above problems. The aim of this research is to apply the MOORA algorithm to help users choose the best e-wallet that suits their needs. For the process of inputting alternative criteria weight values, the results of the system and manual process are the same, according to the results of the validity of the MOORA calculation. Where the application of the MOORA method is carried out by calculating alternative values from the algorithm and weighting, then calculations are carried out to determine the best option. The four e-wallets that are alternatives in this research are GoPay, OVO, ShopeePay, and DANA. Where the application of the Moora method is carried out by calculating alternative values from the algorithm and weighting then, calculations are carried out to determine the best option. The final results of this research showed that Alternative 1 (DANA) was chosen as the best alternative in the Best E-Wallet Selection with a preference value of 0.507.